Exploring the Role of Organizational Communication in Preventing Information Delivery Errors - Ridho, Deri Ainur; Wicaksana, Arief Adji; Hidayat, Rochmat; Rahmaulana, Rima; Amir, Jezzshinta (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study aims to explore the role of organizational communication in preventing communication errors that can negatively affect organizational operations. One of the primary challenges in organizations is communication errors that lead to information distortion, decision-making mistakes, reduced efficiency, and even internal conflicts. In an increasingly complex and dynamic environment, the role of effective communication becomes crucial to ensuring clear and accurate information flow at every organizational level. This research uses a qualitative approach through in-depth interviews and direct observations within public and private organizations to understand the factors influencing communication errors and ways to prevent them. Based on the findings, open communication, the use of appropriate technology, and a supportive organizational culture for two-way communication are key factors in minimizing information errors. The study’s recommendations emphasize the importance of continuous communication training and the development of more transparent communication systems in organization.